Triggering Interest in Learning through Environmentally Based Space Management - Istifadah, Istifadah; Usriyah, Lailatul; Rahmawati, Riyas (JURNAL AL-TANZIM, 2023)
Interest in learning is still a classic problem teachers face in the learning process. The learning environment is one of the school resources that has the potential to arouse students' interest in learning. This research aims to explore and investigate how the design of the physical environment of classrooms or study rooms at the Alam Nurul Islamic School (SANI) Jember can influence students' interests. The research focus was analyzed using the theories of Tomkins, Renninger, Hidi, and several other relevant theories. This research uses a qualitative descriptive method, where data collection is carried out through observation, interviews, documentation, and photography. Data analysis uses the theories of Milles, Huberman, and Saldana with three steps, namely data condensation, data presentation, and verification. The SANI learning environment is managed with the nature-based school concept by utilizing and optimizing the characteristics of the school environment, such as context, content, and learning processes. In this research, strategies, and interventions in the planning and substance of natural environment-based space management by creating a natural learning environment infrastructure can increase students' motivation, attention, and learning experience and potentially increase student interest and engagement.